If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2n+9=6n
We simplify the equation to the form, which is simple to understand
2n+9=6n
We move all terms containing n to the left and all other terms to the right.
+2n-6n=-9
We simplify left and right side of the equation.
-4n=-9
We divide both sides of the equation by -4 to get n.
n=2.25
| 16f=15f+2 | | -10x^2-65x-75=0 | | 10-3r+5+2r= | | h(t)=V*t-16*t^2 | | x-(x+17)=2(11-3x) | | 5=v/20 | | x+6=3-2 | | W-w=3 | | 5n=250 | | 7x+1=15x+3 | | 2(x+3)=6(3) | | f+g/2 | | 1/6+5/12x=5/6 | | -28+15-22z=33 | | (a-5)-3=12 | | 2/3(v-6)=1/3(v+6) | | -(6a+1)+2(3-a)=a | | 14.3-(-21.2)= | | 2(4x+2)=8x+4 | | 4(3+y)=-y+8 | | In=4 | | -15+-18= | | 0+(-10)= | | Y+5=5+y | | 18x^2+11x+15=0 | | 6n-10=22 | | Sinx=4 | | 4(3+y)=y+8 | | 17-5(3x+1)=10*10 | | 4p-2=35 | | X/4=17/2 | | -95-100= |